Factors Affecting the Independence Level of 4-6-Year-Old Children with Cerebral Palsy in Activities of Daily Living - Alvandi, Faeze; Amini , Malek; Ghafarzadeh Namazi , Narges (Iranian Journal of Child Neurology, 2023)
Objectives Enhancing the independence of children with cerebral palsy in their daily activities can significantly alleviate caregiver stress and challenges, thereby improving the quality of life for caregivers.. This study aimed to identify the influential factors in the independence level of children with CP in Activities of Daily Living (ADL) (selfcare) and Instrumental Activities of Daily Living (IADL) (home participation). Materials & Methods In this cross-sectional study, 116 children with different types of CP (61 boys and 55 girls) in the 4-6 age range and their parents were non-randomly selected through convenience sampling. The Iranian-Children Participation Questionnaire was used to measure the children’s independence level in self-care activities and home participation. Several instruments, along with a demographic questionnaire, were used to assess personal factors, such as the Gross Motor Function Classification System, Manual Ability Classification System, Communication Function Classification System, SPARCLE (for determining children’s cognitive level), and Eating and Drinking Ability Classification System. Eventually, the collected data were analyzed using stepwise linear regression Results The results showed that the level of Gross Motor Function Classification System (GMFCS) and Communication Function Classification System (CFCS) and the child’s age had the most correlation with the independence level in self-care activities. Moreover, GMFCS Manual Ability Classification System (MACS), cognitive level, and child’s age were most associated with home participation. Conclusion Personal factors are more effective than environmental factors in determining the independence of children with CP.